2017
DOI: 10.22373/ej.v4i2.1661
|View full text |Cite
|
Sign up to set email alerts
|

Managing Disruptive Behavior of Students in Language Classroom

Abstract: This article describes students' disruptive behaviors in language classroom that may greatly affect language teaching and learning process, especially in ESL or EFL classes. Teachers should know what disruptive behavior is to enable them to deal with problems occurred in their classroom or to take preventive actions to keep their students well-behaved during the class. This can reduce the occurrence of misbehavior of students in their classroom. To prevent disruption in the classroom, teachers should establish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 4 publications
1
11
0
Order By: Relevance
“…This research applied classroom action research to improve 31 students' grammar mastery of reported speech in class XII Social at MAN Kota Blitar by Utilizing Duolingo in Grammar Instruction. The Procedures cycle of this research followed 4 steps by Kemmis and Taggart that covered 1) Planning the Action, 2) Implementing the Action, 3) Observing the Action, and 4 ) Reflecting on the Action Taggart [18]. Those steps are elaborated as follows:…”
Section: Methodsmentioning
confidence: 99%
“…This research applied classroom action research to improve 31 students' grammar mastery of reported speech in class XII Social at MAN Kota Blitar by Utilizing Duolingo in Grammar Instruction. The Procedures cycle of this research followed 4 steps by Kemmis and Taggart that covered 1) Planning the Action, 2) Implementing the Action, 3) Observing the Action, and 4 ) Reflecting on the Action Taggart [18]. Those steps are elaborated as follows:…”
Section: Methodsmentioning
confidence: 99%
“…Concerning the four experiments in the main investigation-two experiments of the main investigation were implemented in Greece before the beginning of the COVID-19 pandemic in February 2020 (one in Athens and one in Thessaloniki) and the other two were in Cyprus at the end of the first wave of the COVID-19 pandemic, when the measures were gradually revoked and it was believed that the pandemic was over in June 2020 (one in Nicosia/Lefkosia and one in Limassol/Lemesos) (Figure 1)-are also considered qualitative due to their form as well as because they create a kind of case study. Admittedly, the main investigation is also characterized as a form of action research [154][155][156][157] due to the fact that (a) the lead researcher correlating to the participants in the framework of interactive teaching as an adult educator (i.e., the lead researcher / adult educator interacted with the participants as facilitator through a continuous dialogue)-in this case it is considered that classroom action research (CAR) is applied [158]; (b) the differentiated teaching methodology is applied [159] (p. 13); and (c) it was used for educators' professional development [159][160][161][162][163][164].…”
Section: Research Approach Methodology-research Methods Audiovisual C...mentioning
confidence: 99%
“…Answers were analyzed using quantitative content analysis (Berelson, 1952;Krippendorff, 1989). The test was comprised of five text vignettes describing typical classroom situations from the area of classroom management, such as dealing with classroom disruptions, off-task behavior or aggression (Khasinah, 2017). Examples of these vignettes can be found in Baier et al (2021).…”
Section: Evidence-based Solutions To Text Vignettesmentioning
confidence: 99%